CHILDREN'S OBLIGATIONS TO THEIR PARENTS IN USTAZ ABDUL SOMAD'S LECTURE WITH A LINGUISTIC CORPUS APPROACH - Aryandi Sudika; Mantasiah R (Curricula: Journal of Teaching and Learning, 2025)
This study examines the construction of children’s obligations toward their parents in the religious sermons of Ustaz Abdul Somad using a linguistic corpus approach. Adopting a quantitative corpus-based design, the research analyzes transcribed sermon texts to identify recurring lexical patterns and semantic associations that frame filial responsibility. Data were collected by transcribing selected sermons and extracting relevant words and phrases related to parental devotion, moral conduct, and religious duty. Corpus analysis software was employed to generate word frequency lists and identify significant collocations, enabling systematic exploration of linguistic patterns across the dataset. The findings reveal that children’s obligations are consistently framed through interconnected moral, religious, social, and spiritual dimensions. High-frequency lexical items and key collocations highlight themes such as obedience, respect, gratitude, sacrifice, and divine accountability. The sermons emphasize filial piety not only as a social expectation but as a theological mandate closely linked to spiritual merit and divine blessing. Recurrent linguistic patterns also demonstrate how persuasive and emotive language reinforces moral urgency and collective responsibility within the audience. This study contributes to corpus linguistics and religious discourse analysis by demonstrating how quantitative linguistic methods can uncover ideological and ethical constructions embedded in sermon texts. It further illustrates how Ustaz Abdul Somad’s language choices shape public understanding and awareness of children’s duties toward their parents, revealing the powerful role of religious discourse in influencing moral cognition and social behavior.